Eine Frage der Liebe - Anderson, Jane 1954-; Lange, Jessica 1949-; Wilkinson, Tom 1948-2023; Panettiere, Hayden 1989-; Brown, Clancy 1959- (Warner Home Video, 2004)
Roy and Irma are a devoted couple living a normal life in rural Illinois. At a party celebrating their 25th wedding anniversary, Roy inexplicably blacks out. As he awakens, it is with the realization that his life must change forever. Roy confesses to Irma that he's a woman trapped in a man's body and that he wants a sex change. A surprise to his wife, turns out to be a shock to the church-going community. Now Roy must face his friends, co-workers and his own children as he confronts his own transformation
Orig.: USA, 2003
Keywords: Fernsehfilm; Gender transition / Drama; Married people / Drama; Families / Illinois / Drama; Gender transition; Families; Married people; Illinois; Comedy films; Drama; Feature films; Film; DVD-Video